86.1k views
2 votes
Solve for m.
9m - (6m - 7) = 2 (m - 3)


1 Answer

2 votes

Answer:


\boxed{\boxed{\tt m=-13}}

Explanation:


\tt 9m-\left(6m-7\right)=2\left(m-3\right)

Expand, Apply the Distributive property:


\tt 9m-\left(6m-7\right)\leadsto \underline{3m+7}


\tt 2\left(m-3\right)\leadsto \underline{2m-6}


\star \:\:\tt 3m+7=2m-6

Subtract 7 from both sides:


\star \:\:\tt 3m+7-7=2m-6-7


\star \:\: \tt 3m=2m-13

Subtract 2m from both sides:


\star \:\: \tt 3m-2m=2m-13-2m


\star \:\: \tt m=-13

_____________________________

User Mel Gerats
by
4.7k points